2015
DOI: 10.1111/ajt.13222
|View full text |Cite
|
Sign up to set email alerts
|

Hcmv-miR-UL22A-5p: A Biomarker in Transplantation With Broad Impact on Host Gene Expression and Potential Immunological Implications

Abstract: Cytomegalovirus (CMV) encodes multiple microRNAs. While these have been partially characterized in vitro, their relevance to clinical CMV infection has not been evaluated. We analyzed samples from a cohort of solid organ transplant patients with CMV disease (n = 245) for viral microRNA expression. Several CMV microRNAs were readily detectable in patients with CMV disease in variable relative abundance. Expression level generally correlated with DNA viral load and the absence of viral microRNA was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
5
24
2
Order By: Relevance
“…Notably, we also observed relatively lower unstable miRNA expression in the blood, which differs greatly from observations in lungs and livers. Several circulating HCMV miRNAs have been previously described as potential biomarkers, and were associated with hypertension, diabetes, and transplantation [25,45,46]. In those studies, miRNA expression was not detected in certain patient blood samples, consistent with our observations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Notably, we also observed relatively lower unstable miRNA expression in the blood, which differs greatly from observations in lungs and livers. Several circulating HCMV miRNAs have been previously described as potential biomarkers, and were associated with hypertension, diabetes, and transplantation [25,45,46]. In those studies, miRNA expression was not detected in certain patient blood samples, consistent with our observations.…”
Section: Discussionsupporting
confidence: 91%
“…In those studies, miRNA expression was not detected in certain patient blood samples, consistent with our observations. Therefore, viral miRNA expression in the blood appears to change constantly and may be subject to multiple regulatory mechanisms [25]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the majority of the 5 miRNAs identified in our study have been reported to be related to some HCMV infection diseases, for instance, hcmv-miR-UL22a-5p may be a potential predictor of clinical and virological endpoint in solid organ transplant patients [31], and increased hcmv-miR-UL112-3p was also reported to be related with glioblastoma, rheumatoid arthritis, diabetes mellitus essential hypertension as well as congenital infection [18, 19, 32]. All these results indicate that these HCMV encoded miRNAs may share similar physiological and pathological roles in HCMV infection related diseases as well as in OLP, eventhough much further study is needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%